USING OF HEURISTIC JUDGMENT IN CHOOSING ANSWERS OF CONCEPTUAL UNDERSTANDING TEST - MOCHAMAD HERLAN; DINNY DEVI TRIANA; RIYADI; MUHAMAD SUHARDI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
This article presents the cognitive load in choosing answers to conceptual understandingtest of the human regulatory system. The purpose of this study is to find the influence ofcognitive load directly and indirectly on the variables that are identified. The research methodused was survey research and analyzed based on the path coefficient with the 8.72 Lisrelprogram. The population in this study are students of class XI science from three schools inKabupaten Serang a numbers of 463 students and the sample taken a numbers of 215 students.The results of this study indicate that there is a direct influence of cognitive load on heuristicjudgment. The effect directly have a significant positive effect directly, namely cognitive loadon working memory, and working memory on heuristic judgment. One hypothesis had asignificant indirect effect, namely cognitive load on heuristic judgment through workingmemory.